2013
DOI: 10.5152/tud.2013.055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prostate weight on the outcomes of robot-assisted radical prostatectomy

Abstract: Objective: The effect of prostate volume on the surgical, functional, and oncological outcomes of robot assisted radical prostatectomy (RARP) was evaluated. Material and methods:A total of 180 patients who underwent RARP and had at least a 1-year follow-up were included. The patients were divided into 3 groups based on prostate weight (Group 1: <45 g, Group 2: 45-75 g, and Group 3: >76 g). Erectile function and continence were evaluated at 3, 6, 9, and 12 months postoperatively. The International Index of Erec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The mean console time and mean estimated blood loss were significantly increased with increasing prostate weight in our study. Boylu et al [9] and Yasui et al [10] reported that the greater the prostate weight, the longer the operative time, and Hirasawa et al [11] reported that the greater the prostate weight, the more the blood loss, as it is thought that men with enlarged prostate glands usually have more vascularity and broader resection margins. However, the transfusion rate was not significantly associated with the prostate weight, so even though there is a greater amount of bleeding with a greater prostate weight, it would not be clinically meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…The mean console time and mean estimated blood loss were significantly increased with increasing prostate weight in our study. Boylu et al [9] and Yasui et al [10] reported that the greater the prostate weight, the longer the operative time, and Hirasawa et al [11] reported that the greater the prostate weight, the more the blood loss, as it is thought that men with enlarged prostate glands usually have more vascularity and broader resection margins. However, the transfusion rate was not significantly associated with the prostate weight, so even though there is a greater amount of bleeding with a greater prostate weight, it would not be clinically meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 months, the continence rate was 97% in the group with lower prostate volume and 84% in the group with higher volume (p<0.05) (11). In addition to studies showing that smaller prostate volume has a favorable impact on post-RALRP urinary continence, the literature also includes studies in which prostate volume was not a significant factor in continence (12,13,14). Similar to the work of Labanaris et al (13) and Yasui et al (14) the results of our study suggest that prostate volume is not a determining factor in postoperative continence.…”
Section: Discussionmentioning
confidence: 99%